2017
DOI: 10.1016/j.numecd.2017.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Low vitamin D status in relation to cardiovascular disease and mortality in Swedish women – Effect of extended follow-up

Abstract: Low 25D status increased the risk for all endpoints, but a lengthy follow-up diminished these risks towards the null. The impact of follow-up depends on the outcome. Future studies of 25D and disease should use repeated 25D assessments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…It has been suggested that low SES is associated with low levels of vitamin D, which could explain some of Side 15 af 26 these findings; however, this wasn't investigated in the present study [31].…”
Section: Discussionmentioning
confidence: 62%
“…It has been suggested that low SES is associated with low levels of vitamin D, which could explain some of Side 15 af 26 these findings; however, this wasn't investigated in the present study [31].…”
Section: Discussionmentioning
confidence: 62%
“…Most studies reported inverse associations between 25(OH)D concentration and all-cause mortality (i.e. higher mortality for lower 25(OH)D) (Figure 2 and Table S2) [6,10,11,22,23,24,26,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61]. These studies generally had long follow-up times, substantial numbers of participants and deaths, extensive adjustment for potential confounders, and encompassed broad geographical regions including North America, South America, Europe, Asia, and Australia, although the vast majority of studies were conducted in Europe and the United States (U.S.).…”
Section: Resultsmentioning
confidence: 99%
“…Leu-Agelii et al (2017) examined whether the duration of follow-up affected the association between 25(OH)D and all-cause mortality in the Population Study of Women in Gothenburg with more than 30 years of follow-up. The association remained, but was attenuated with longer follow-up time (HRs at 17 years and 37 years for the lowest versus upper three 25(OH)D fourths = 1.96, 95% CI 1.25–3.08 and 1.42, 95% CI 1.17–1.72, respectively) [40].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There, it is converted to 25-hydroxyvitamin D (25[OH]D) by a hydroxylase and subsequently to the biologically active 1,25-dihydroxycholecalciferol (1,25[OH]2D3) by hydroxylation in the kidneys (9). Vitamin D deficiency is associated with hypertension, diabetes, cardiovascular disease, and cancer (10)(11)(12), as well as bone diseases such as rickets in children and osteomalacia in adults (13). In addition, vitamin D is reported to be associated with muscle mass.…”
mentioning
confidence: 99%